2020
DOI: 10.3390/su12135457
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Technological Processes on Odorant Emissions at Municipal Waste Biogas Plants

Abstract: Municipal waste treatment is inherently associated with odour emissions. The compounds characteristic of the processes used for this purpose, and at the same time causing a negative olfactory sensation, are organic and inorganic sulphur and nitrogen compounds. The tests were carried out at the waste management plant, which in the biological part, uses the methane fermentation process and is also equipped with an installation for the collection, treatment, and energetic use of biogas. The tests include … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…Selective collection of composite packaging began in the service area only in June 2020. At the biogas plant analysed in [16], VOC emissions from the waste storage hall were reported at a similar level, in the range of 150-415 g/h (average 298 g/h, RSD 245%). At other biogas plants processing mixed MSW, the VOC emission values from above mixed MSW in the unloading and storage hall were set at a slightly lower level; they were 25-106 g/h (average 54 g/h, RSD 44%) in the case of one biogas plant, and 11-264 g/h (average 102 g/h, RSD 81%) in the case of the second tested biogas installation [17].…”
Section: Resultsmentioning
confidence: 77%
See 1 more Smart Citation
“…Selective collection of composite packaging began in the service area only in June 2020. At the biogas plant analysed in [16], VOC emissions from the waste storage hall were reported at a similar level, in the range of 150-415 g/h (average 298 g/h, RSD 245%). At other biogas plants processing mixed MSW, the VOC emission values from above mixed MSW in the unloading and storage hall were set at a slightly lower level; they were 25-106 g/h (average 54 g/h, RSD 44%) in the case of one biogas plant, and 11-264 g/h (average 102 g/h, RSD 81%) in the case of the second tested biogas installation [17].…”
Section: Resultsmentioning
confidence: 77%
“…According to Turin and Yoshii [15], odorants are characterised by properties such as volatility, hydrophobicity, and a molecular weight of less than about 300 g/mol. The odour impact of waste treatment plants is mainly influenced by such factors as the technology used, type of waste, technological regime, the occurrence of failure of technological lines or their elements, temperature, and relative humidity of the air, as well as compliance of plant employees with the technological regime [16][17][18].…”
Section: Introductionmentioning
confidence: 99%
“…The scope of the research includes both physical and chemical parameters of technological wastewater and gases emitted from the tank into which sew-age flows. The odorant concentration: ammonia (resolution: 1.0 ppm), volatile organic compounds (resolution 10 ppb), hydrogen sulphide (resolution: 0.1 ppm) and methyl mercaptan (resolution: 0.1 ppm) were determined using the MultiRae Pro portable gas detector with build-in a pumping system in five repetitions at each measurement site [26].…”
Section: Study Methodologymentioning
confidence: 99%
“…For example, Wisniewska et al (2020) monitored odors and malodorous compounds in different parts of an anaerobic digestion plant treating food waste. The authors concluded that the zone of waste collection was the main emissions source of the plant [62]. In another similar study [63], waste storage, fermentation preparation, and digestate dewatering were the main emission odor sources in a Polish MSW biogas treatment plant, with ranges of 4 to 78 ou/m 3 for fermentation preparation and from 8 to 448 ou/m 3 for digestate dewatering.…”
Section: Anaerobic Digestionmentioning
confidence: 96%